Ideas of Sheikh Isma’il Idris Bin Zakariyya: Legacy for Progressive Contemporary Islamic Movement - Suleiman, Ibrahim (International Journal of Islamic Business & Management, 2018)
This paper discussed the role and ideas of Sheikh Isma’il Idris in religionand politics in Nigeria. It is very paramount that Islamic scholars are considered to be relevant in modelling the minds of Muslims Ummah towards participation in politics and electoral process. Therefore, this article highlights the major contributions made by this Islamic scholar and outlines his role in terms of revivalism during his life-time and beyond. This is accomplished by investigating his major works and his teachings especially in shaping participation in political circle so as to ensure that Muslims are participated in the political and electoral process in Nigeria. In his political thought, Sheikh Idris believed strongly in Muslim’s participation in politics and governance as against the otherviewsof anti-democratic arguments. His major concern is to encourage Muslims Ummah particularly the youths to participate in government activities in order to protect the interest of their religion considering the diverse nature of the country. Hence, assessing his role and ideas will significantly improve our understanding of Islamization movement towards determining social reality, justice and equity along Islamic ethics and values.